Quality enhancement of Barramundi kamaboko using vortex fluidic device modified starch and fish gelatin - Lin, Jiayi; Wu, Yixiao; Wang, Hao; Jellicoe, Matt; He, Shan; Young, David J.; Thennadil, Suresh; Raston, Colin L.; Brennan, Charles; Tian, Bin; Abukhadra, Mostafa R.; El-Sherbeeny, Ahmed M. (Frontiers in Sustainable Food Systems, 2024)
Introduction Prime quality kamaboko (cooked surimi) is produced from Alaska pollock. The main challenge of using cheaper fish fillets, including Barramundi, is achieving similar textures. Methods Combined with fish gelatin, modified starch by vortex fluidic device was used to enhance the quality of kamaboko made from Barramundi. Results Modification by a continuous flow vortex fluidic device (VFD) significantly reduces the size of particles of starch relative to conventional homogenization. Blending this VFD-modified starch with fish gelatin resulted in a well-organized cross-linked matrix compared to products manufactured from homogenization modified starch. This led to higher gel strength of the former (1,708.32 g/cm2) relative to the latter (832.56 g/cm2). Mixing different proportions of fish gelatin and VFD-processed starch to make Barramundi kamaboko (5, 10, and 15%), yielded a product with greater chewiness relative to Alaska pollock kamaboko. Sensory evaluation indicated that the 5% product was optimal and the 15% product with the highest chewiness (56.10 N) was the least favorable. Discussion These results clearly indicate the potential of VFD processed starch, blended with fish gelatin to enhances the quality of kamaboko.